COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.